The Sanctuary of Demeter and Kore : The Inscriptions XVIII.6. - Stroud, Ronald S.; American School of Classical Studies at Athens (Havertown: American School of Classical Studies at Athens, 2013)
"Excavations conducted by the American School of Classical Studies at Athens in the Sanctuary of Demeter and Kore on Acrocorinth, 1961-1975, produced more than 170 inscribed objects of stone, bronze, bone, lead weights, pottery (graffiti and dipinti), clay pinakes, magical lead tablets, and in a mosaic. In this new Corinth volume, Ron Stroud presents all of these inscriptions, and he relates them to an overall interpretation of the activities, secular and religious, attested in this shrine during its long period of use from the 7th century B.C. until the end of the 4th century A.D. Where possible, Stroud also draws out their implications for and contribution to the history of ancient Corinth, the worship of the goddesses Demeter and Kore, and the practice of magic--especially in the Roman period. This is the final publication of the inscribed objects from the sanctuary, excluding loomweights and stamped amphora handles, which will be included in a later publication." -- Publisher website. Excavations conducted by the American School of Classical Studies at Athens in the Sanctuary of Demeter and Kore on Acrocorinth, 1961-1975, produced more than 170 inscribed objects of stone, bronze, and bone, as well as lead weights, mosaics, dipinti and graffiti on pottery, clay pinakes, and magical lead tablets. All of the inscriptiopns in this volume are transcribed, and the author relates them to an overall interpretation of the activities, secular and religious, attested in this shrine during its long period of use from the 7th century B.C. until the end of the 4th century A.D. Where possible, the author also draws out their implications for and contribution to the history of ancient Corinth, the worship of the goddesses Demeter and Kore, and the practice of magic, especially in the Roman period. This is the final publication of all the inscribed objects from the sanctuary, excluding stamped amphora handles and loomweights, which will be included in a later fascicle.
Introduction -- Inscriptions on stone, metal, bone, and in mosaic -- Dipinti on pottery -- Graffiti on pottery -- Inscriptions on clay pinakes -- Magical lead tablets -- Concordances -- Indexes -- General index -- Index of ancient sources -- Index of Greek and Latin names -- Index of Greek and Lain words.
Includes bibliographical references and indexes.
Keywords: Sanctuary of Demeter and Persephone (Corinth, Greece); Inscriptions, Greek -- Greece -- Corinth; Inscriptions, Latin -- Greece -- Corinth; Excavations (Archaeology) -- Greece -- Corinth; Material culture -- Greece -- Corinth; ART / History / Ancient & Classical; Architecture / History / General; Corinth (Greece) -- Antiquities